2015
DOI: 10.3899/jrheum.150071
|View full text |Cite
|
Sign up to set email alerts
|

No Association between Daily Walking and Knee Structural Changes in People at Risk of or with Mild Knee Osteoarthritis. Prospective Data from the Multicenter Osteoarthritis Study

Abstract: Objective We investigated the association between objectively measured daily walking and knee structural change, defined either as radiographic worsening or as cartilage loss, in people at risk of or with knee osteoarthritis (OA). Methods Participants from the Multicenter Osteoarthritis (MOST) study with Kellgren and Lawrence (KL) grades 0–2 and daily walking (measured with the StepWatch) at the 60-month visit, were included. Participants had fixed flexion weight bearing radiographs and knee magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 51 publications
1
26
1
Order By: Relevance
“…This is somewhat consistent with a previous study which reported that patients with all grades of OA severity on MRI could benefit from professional supervised exercise therapy, although the effects might be reduced in patients with advanced patellofemoral osteoarthritis (PF OA) 46 . The Multicentre Osteoarthritis (MOST) study reported no association between daily walking and structural changes over 2 years in people at risk of mild knee OA 47 , however, this study was limited by the assessment of a narrow range of step frequency.…”
Section: Discussionmentioning
confidence: 88%
“…This is somewhat consistent with a previous study which reported that patients with all grades of OA severity on MRI could benefit from professional supervised exercise therapy, although the effects might be reduced in patients with advanced patellofemoral osteoarthritis (PF OA) 46 . The Multicentre Osteoarthritis (MOST) study reported no association between daily walking and structural changes over 2 years in people at risk of mild knee OA 47 , however, this study was limited by the assessment of a narrow range of step frequency.…”
Section: Discussionmentioning
confidence: 88%
“…Our findings are in keeping with the few previous studies that utilized objective measures of physical activity. In the MOST Study, in persons at higher risk or with mild OA, there was no association between daily walking, measured objectively using a StepWatch or with time spent walking at a moderate to vigorous intensity at the 60‐month visit and radiographic progression by the 84‐month visit . In OAI participants at higher risk of knee OA but free of the outcome of interest, ≥150 minutes per week of moderate‐vigorous physical activity was not associated with incident radiographic knee OA, symptomatic knee OA, or joint space narrowing versus <10 minutes of moderate‐vigorous activity per week .…”
Section: Discussionmentioning
confidence: 91%
“…In OAI participants at higher risk of knee OA but free of the outcome of interest, ≥150 minutes per week of moderate‐vigorous physical activity was not associated with incident radiographic knee OA, symptomatic knee OA, or joint space narrowing versus <10 minutes of moderate‐vigorous activity per week . Longitudinal studies using MRI‐based outcomes have also mostly relied on self‐reported physical activity , with some exceptions ; these studies have had mixed results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been reported that abnormal findings on simple X-ray and MRI examinations may not necessarily match subjective pain and clinical symptoms13 ) . In this study, all measurements were taken at a regional community center rather than at a medical venue; therefore the following method for simple knee-joint malalignment assessment was used.…”
Section: Methodsmentioning
confidence: 99%